Symmetry Breaking in Cells and Tissues - Goryachev, Andrew (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
"Symmetry Breaking in Cells and Tissues" presents a collection of seventeen reviews, opinions and original research papers contributed by theoreticians, physicists and mathematicians, as well as experimental biologists, united by a common interest in biological pattern formation and morphogenesis. The contributors discuss diverse manifestations of symmetry breaking in biology and showcase recent developments in experimental and theoretical approaches to biological morphogenesis and pattern formation on multiple scales.